The voting booth - Colbert, Brandy (Hyperion, an imprint of Buena Vista Books, Inc., 2020)
The first year they are eligible to vote, Marva and Duke meet at their polling place and, over the course of one crazy day, fall in love.--
Keywords: Politics, Practical / Juvenile fiction; African Americans / Juvenile fiction; Elections / Juvenile fiction; Interpersonal relations / Fiction; Love / Fiction; YOUNG ADULT FICTION / Social Themes / Prejudice & Racism; YOUNG ADULT FICTION / Politics & Government; YOUNG ADULT FICTION / Romance / Contemporary; Young adult fiction; Young adult works; Fiction; Juvenile works; Romance fiction; Love stories; Novels; Jugendbuch